Comparison between different parameters for anaerobic digestion technologies - Rabaa K AL-Farajat; Mohamed R Gomaa (Global Journal of Ecology - Peertechz Publications, 2022)
Due to the increased demand for energy and the near depletion of fossil fuel sources, in addition to the problems of global warming, the world has turned to renewable energy sources as an alternative solution. One energy source is the anaerobic digestion of organic matter, such as animal or food waste. Biogas is produced from this process, used to generate electricity and heat, or processed for use as a transportation fuel and compost production for agriculture. This process is affected by many factors like the potential of hydrogen (PH), temperature, carbon/nitrogen ratio (C/N), and other factors. Dry anaerobic digestion has higher total solid content (TS) than wet anaerobic digestion. On the other hand, it has lower maintenance and construction costs compared with wet anaerobic digestion. In this research, we will highlight the operational conditions of the process in addition to its different types. It also contains an overview of this system, its working principle, its advantages, and the system component and show the best ways to improve its efficiency.